EVALUASI PEMANFATAN DANA INSENTIF DAERAH BERBASIS PENGHARGAAN PEMBANGUNAN DAERAH PADA PROVINSI JAWA TENGAH, BENGKULU DAN JAWA TIMUR - Andi Setyo Pambudi; Grace Second Lady Manalu; Deni . (Jurnal Kebijakan Pemerintahan, 2022)
Abstract Inequality of regional development related to fiscal disparity has been a problem until now. The fiscal decentralization development is not only related to the fund's transfer to regional governments but also attention to creating positive impacts on the quality of public services improvement and regional economic growth. At the provincial level, the Regional Incentive Funds is one of the sources of regional development funding and as a measure of regional quality because to obtain it requires competition. One of the competitions that become the basis for calculating the allocation of Regional Incentive Funds is the Regional Development Award organized by the Ministry of National Development Planning/Bappenas. The evaluation related to Regional Incentive Funds aims to assess the realization quality and effectiveness of Regional Incentive Funds utilization in 2021 by the best provinces in Regional Development Awards 2020, which become interesting to review to strengthen cooperation between the central and regional governments and increase these funds utilization in the regions. This study uses a quantitative descriptive method approach from the google form questionnaire and Zoom application as a limited verification of Regional Incentive Funds recipients in 2021, especially the top 3 best provinces in Regional Development Awards 2020, to see field implementation related to policy changes that affect the Regional Incentive Funds implementation during the COVID-19 Pandemic in the context of ongoing evaluation. The analysis results show that although the realization in the 3 (three) provinces is considered good, the Regional Incentive Funds utilization is not well planned when compared to other transfer funds, such as the Special Allocation Fund (DAK), whose planning, implementation, and evaluation processes are carried out more tiered and use a more established system. Keywords: Regional Incentive Funds, Regional Development Awards, Province, Evaluation